Sporotrichosis, a public health problem: Review - Tóffoli, Estéfani Longo; Ferreira, Franciane de Moraes Santos; Cisi, Vivian Lindmayer; Domingues, Leslie Maria (Pubvet, 2022)
Sporotrichosis is a fungal disease that affects humans and animals, especially cats. Considered a neglected zoonosis, the infection has increased in Brazil. A disease once considered rare, today is endemic in several states, especially in Rio de Janeiro with 3,291 confirmed cases between 2015 and 2017. Despite of that, awareness of the disease among population is scarce, which aggravates its spread. This work aims to describe a literature review on human sporotrichosis in Brazil.
Keywords: Epidemic; sporotrichosis; mycosis; zoonosis